2009
DOI: 10.1073/pnas.0907812106
|View full text |Cite
|
Sign up to set email alerts
|

Selective activation of FGFR4 by an FGF19 variant does not improve glucose metabolism in ob/ob mice

Abstract: FGF19 is a hormone that regulates bile acid and glucose homeostasis. Progress has been made in identifying cofactors for receptor activation. However, several functions of FGF19 have not yet been fully defined, including the actions of FGF19 on target tissues, its FGF receptor specificity, and the contributions of other cofactors, such as heparin. Here, we explore the requirements for FGF19-FGFR/co-receptor interactions and signaling in detail. We show that ␤Klotho was essential for FGF19 interaction with FGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
92
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(107 citation statements)
references
References 21 publications
12
92
3
Order By: Relevance
“…1 summarizes the effects of hFGF19 at nanomolar concentrations. Our findings are consistent with those of earlier studies, which examined the activity of hFGF19 at concentrations ranging from 10 to 100 nM (15,26,27). However, hFGF19 concentrations in the human circulation are reportedly in the subnanomolar range, most likely around 30 pM, which is 3-4 orders of magnitude lower than the concentrations tested previously (28 -30).…”
Section: Resultssupporting
confidence: 93%
“…1 summarizes the effects of hFGF19 at nanomolar concentrations. Our findings are consistent with those of earlier studies, which examined the activity of hFGF19 at concentrations ranging from 10 to 100 nM (15,26,27). However, hFGF19 concentrations in the human circulation are reportedly in the subnanomolar range, most likely around 30 pM, which is 3-4 orders of magnitude lower than the concentrations tested previously (28 -30).…”
Section: Resultssupporting
confidence: 93%
“…By binding to FGFR4, FGF19 inhibits CYP7A1, the rate limiting enzyme of bile acid biosynthesis, thus inhibiting bile acid synthesis. In addition, previous study showed that selective activation of FGFR4 failed to improve glucose metabolism in ob/ob mice [11]. Thus,…”
mentioning
confidence: 93%
“…protocol, and treated with various FGF molecules as previously described ( 15 ). Cells were collected 15 min after treatment, snap frozen in liquid nitrogen, and resuspended in lysis buffer, and the total and phosphorylated ERK were measured using an MSD whole cell lysate Phospho-ERK1/2 kit (Meso Scale Discovery) according to the manufacturer's instructions.…”
mentioning
confidence: 99%